Performans Pertumbuhan Babi Lokal Jantan yang Mengonsumsi Pakan Olahan Biji Asam dalam Ransum - Redempta Wea (Politeknik Pertanian Negeri Kupang, 2013)
The aim of this research was conducted growth performance of local male pig that concumption of fermented tamarind seed in ration. This research has been conducted in Polytechnic of Agriculture Kupang from April until September 2012. The materials that used was 21 male local pigs (grower pigs), tamarind seed, tempe yeast, tunggak bean, rice bran, corn meal, meat bone meal, vitamin-mineral premix, and vegetable oil. The variable being measured were dry matter consumption, daily gain, and feed convertion. Research result showed the treatments did not significantly affect (P>0,05) dry matter consumption (299,89 g/ekor/hari-386,66 g/ekor/hari), daily gain (109,33 g/ekor/hari-133,33 g/ekor/hari), and feed covertion (2,76-3,50) of male local pigs and the best growth performance was showed by 20% fermentation or not fermentation tamarind seed in feed. Therefore it is suggested that the addition of tamarind seed will not exceed 20% into consumption. Key words : Local male pig, tamarind seed, tempe yeast, growth performance